Finite element analysis model of corrosion fatigue for TIG welding workpiece - Limwongsakorn S. (2017)
© 2016 Trans Tech Publications. The proposed finite element analysis (FEA) model was constructed using FEA simulation software, ANSYS program, for determining effects of corrosion fatigue (CF) from TIG welding process on AISI 304 stainless steel workpiece. The FEA model of TIG welding process was developed from Goldak's double ellipsoid moving heat source. In this paper, the residual stress results obtained from the FEA model were consistent with results from the X-ray diffraction (XRD) method. The residual stress was further used as an input in the next step of corrosion fatigue analysis. The predictive CF life result obtained from the FEA CF model were consistent with the value obtained from stress-life curve (S-N curve) from the reference literaturature. Therefore, the proposed FEA of CF model was then used for predicting the corrosion fatigue life on TIG welding workpiece, the results from the model showed the corrosion fatigue life of 1,794 cycles with testing condition of the frequency (f) = 0.1 Hz and the equivalent load of 67.5 kN (equal to 150 MPa) with R = 0.25.